ANALISIS PENGARUH HARGA, LOKASI DAN FASILITAS TERHADAP MINAT BELI KONSUMEN PADA LAPANGAN ALL STAR FUTSAL PADANG - Doni Romatua; Nurlina Nurlina (JURNAL AKUNTANSI BARELANG, 2019)
This study aims to identify and analyze the effect of price, location and f asilitas partially and simultaneously on consumer buying interest in the field of All Star Futsal Padang. The method used is quantitative descriptive. The sampling technique used is non-probability sampling, so that the population is taken from a sample of 100 respondents. Data analysis techniques used are multiple linear regression, t test, F test and coefficient of determination. Based on the multiple linear regression analysis of the variables of price, location and amenities on consumer buying interest in the field of All Star Futsal Padang obtained Y = 4.476 + 0.176 + 0.239 X 1 X 2 + 0.371 X 3 + e. From the results of the t test conducted at variable rates had no significant effect on consumer buying interest with a value of t <t table (1,386 <1.6 60), and the location variables have a significant effect on consumer buying interest with t count> t table (2,223 > 1.660), and the facility variables significantly influence consumer purchase interest with t count> t table (4.900> 1.660). From the results of the F test or tests performed simultaneously proved that the variable price, location and f asilitas have F count> F table or 34.626> 2.70, thus simultaneously a significant effect on consumer buying interest in the field of All Star Futsal P adang, while the coefficient of determination obtained Adjusted R Square of 50.5% is 49.5% explained by other variables that are not addressed in this study.